PENGETAHUAN DAN SIKAP IBU PRIMIGRAVIDA TENTANG CARA MENGATASI MASALAH FISIOLOGIS PADA KEHAMILAN TRIMESTER SATU - Hermina Humune (Akademi Kebidanan Griya Husada Surabaya, 2017)
The occurrence of pregnancy causes changes in hormonal balance, especially changes in the hormones estrogen and progesterone. Not many women who undergo pregnancy without pain or pain, but generally feel a variety of minor complaints. As an impact of the physiological changes of pregnancy that are felt by pregnant women in the first trimester and expressed by complaints such as nausea, vomiting, frequent urination, headaches, etc. According to the medical record in BP Anurul, it was found that mothers experienced many complaints during pregnancy, according to an initial survey of 10 primigravida mothers about knowledge on how to overcome the physiological problems of first trimester pregnancy, the majority of mothers had less knowledge (50%). Whereas about attitude, the majority of mothers have disagreements as much (50%). This study aims to describe the knowledge and attitudes of primigravida mothers on how to overcome the physiological problems of first trimester pregnancy. . Method: This study uses a descriptive non-probability sampling design, the sampling technique is saturated sampling with a sample of 30 people. Research instrument uses primary data (questionnaire). The results are processed in the frequency table and cross tabulation. Results: The results showed that the majority of the less knowledgeable mothers could not overcome the physiological problems of the first trimester of pregnancy (81.3%) compared to the majority of good knowledge mothers who were able to overcome the first trimester physiological problem (66.7%). the majority cannot overcome the physiological problems of the first trimester of pregnancy (87.5%) compared to those who have a very agreeable attitude the majority can overcome the first trimester physiological problem namely (80%). Discussion: Knowledge and attitudes of mothers influence the way mothers deal with physiological problems in pregnancy. Therefore efforts are made to increase knowledge and attitudes about the importance of prenatal care through the provision of information on health care during pregnancy.